Simple fabrication of nanogratings using flexible polydimethylsiloxane film. (18th February 2019) - Zhang, Yaoju; He, Xin; Jiang, Tao; Zhuang, Youyi; Fang, Chaolong
Abstract: The fabrication of nanogratings usually requires expensive equipment such as electron beam lithography. Here, a novel and simple method of fabricating nanogratings is presented by contracting the prestretched polydimethylsiloxane (PDMS) substrate adhered a unstretched PDMS micrograting film which is obtained by replicating the template fabricated from less expensive laser beam lithography. Additionally, a PDMS gradient-pitch nanograting is successfully fabricated by adhering a unstretched micrograting PDMS film onto a prestretched wedge-shaped PDMS substrate. The proposed method shows great promise in optical applications requiring cost-effective and accurate nanogarings and filters.